Die Scilly-Inseln - Leuze, Eva (ERDKUNDE, 1966)
The Isles of Scilly experience a maritime climate, similar to that in parts of Chile and New Zealand, with a low annual range of temperature. Due to this flowers can be grown and harvested in winter, when they sell at a high price in the big cities of England. To protect the delicate daffodils from Atlantic gales, high evergreen windbreaks are grown around the fields - mainly of plants from the southern hemisphere, such as Pittosporum, Euonymus, Veronica, and Escallonia. The effect of the climate, especially the wind, on the vegetation of the islands is dealt with. Over 90% of the population used to be engaged in the flower trade as their only means of living. During recent years the tourist industry has become more and more important, claiming labour that is needed on the flower farms. Young people leave their homes to have their secondary education in Doarding schools on the mainland. This means that most of them will never return to their homes, having trained for professions for which there are no opportunities in the islands. Shortage of labour and bad flower seasons will encourage many farmers to take in visitors during the summer, to the detriment of the flower industry. Communications have altered greatly. Tourism has invaded the shores of these islands; it might have the effect of superseding the still flourishing 80 year old flower trade - a new change in the ever changing economy of the islands. This is characteristic of all marginal areas, where life is hard and people have to adapt themselves to circumstances in order to find the best way of gaining a living.